Mechanical performances of continuous carbon fiber reinforced PLA composites printed in vacuum. (15th November 2021) - Li, Huimin; Liu, Baosheng; Ge, Lei; Chen, Yi; Zheng, Huayong; Fang, Daining
Abstract: The main objective of this paper is to investigate the mechanical performance of the continuous carbon fiber reinforced PLA composites (CFRPCs) printed in vacuum. A novel 3D printer which is used to manufacture CFRPCs in vacuum and a continuous carbon fiber prepreg filament production equipment which is used to produce the raw materials needed for 3D printing are first proposed. Compared with the printing in atmospheric environment, the impregnation effect of the part printed in vacuum can be effectively improved, the porosity is reduced from 13.93% to 4.18%, and the flexural strength and modulus are increased by 24.51% and 8.35%, respectively. The influences of 3D printing process parameters on the mechanical properties of the specimens printed in vacuum are systematically researched. The flexural properties of the specimens are positively correlated with the printing temperature and inversely related to the printing speed and layer thickness. When the printing temperature increases from 180 °C to 230 °C, the flexural strength and flexural modulus of the printed parts are increased by 45.73% and 31.75%, respectively. The feasibility of 3D printing continuous carbon fiber reinforced thermoplastic (CFRTP) in vacuum is demonstrated.